How Informed are the Swiss about Covid-19 and Prevention Measures? - Sabrina Heike Kessler; Miriam S. Cano Pardo; Anna Jobin; Fanny Georgi (University of Zurich, IKMZ - Department of Communication and Media Research, 2022)
Since the coronavirus (SARS-CoV-2) pandemic began, large amounts of (mis)information have been disseminated worldwide. We conducted an online survey in Switzerland (N = 1,129) in April 2021 to ask respondents which information has received too little attention in public discourse, which measures help containing coronavirus infection and Covid-19, and about subjectively perceived Covid-19 misinformation. Content analysis of the open answers revealed that vaccination and its potential side effects, aspects related to political measures, psychological and social aspects, as well as science and research topics deserved more attention in the eyes of the respondents, mostly from politics or media. The most frequently mentioned effective measures were social distancing, wearing masks, general hygiene, and vaccination. Notably, the number of measures mentioned was related to the degree to which the pandemic affected individuals subjectively, trust in public institutions, and their individual level of science-related populism. Swiss residents with less trust in public institutions and who consume less news media on Covid-19 are more likely to believe misinformation on (in)effective measures against the virus. Most respondents encountered Covid-19 misinformation and could name examples, including sources. Education and information use affect the frequency of subjectively encountered misinformation. More highly educated people can name more misinformation instances encountered than less educated people.